2020
DOI: 10.3389/fped.2020.579924
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Considerations for Diagnosing Rare Diseases in Indigenous Populations

Abstract: Advances in omics and specifically genomic technologies are increasingly transforming rare disease diagnosis. However, the benefits of these advances are disproportionately experienced within and between populations, with Indigenous populations frequently experiencing diagnostic and therapeutic inequities. The International Rare Disease Research Consortium (IRDiRC) multi-stakeholder partnership has been advancing toward the vision of all people living with a rare disease receiving an accurate diagnosis, care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…A 2016 update showed that White participants continued to make up 81% of all samples in GWAS studies while comprising only 16% of the global population; in comparison, Black and Hispanic subjects comprised only 2% and < 0.5%, respectively (Martin et al 2019). Indigenous American and Pacific Islander populations experience particular challenges in accessing testing; we found that Native American and Native Hawaiian groups are barely represented at all in the literature, comprising a mere 0.01% of all subjects reported (D'Angelo et al 2020).…”
Section: Discussionmentioning
confidence: 64%
“…A 2016 update showed that White participants continued to make up 81% of all samples in GWAS studies while comprising only 16% of the global population; in comparison, Black and Hispanic subjects comprised only 2% and < 0.5%, respectively (Martin et al 2019). Indigenous American and Pacific Islander populations experience particular challenges in accessing testing; we found that Native American and Native Hawaiian groups are barely represented at all in the literature, comprising a mere 0.01% of all subjects reported (D'Angelo et al 2020).…”
Section: Discussionmentioning
confidence: 64%
“…The initiative will expand region wide awareness to the issues, opportunities and challenges of rare diseases by encouraging awareness and advocacy. There is the need to provide greater access and options for diagnosis and treatment to all patients, including indigenous people 30 …”
Section: Meeting Global Needs and Developing Nationsmentioning
confidence: 99%
“…18 Indigenous American and Paci c Islander populations experience particular challenges in accessing testing; we found that Native American and Native Hawaiian populations are barely represented at all in the literature, comprising a mere 0.01% of all subjects reported. 19 This trend in racial/ethnic disparities has been well described in genetic testing for other diseases. Broadly, patients of African and Asian ancestry are more likely than those of European ancestry to receive ambiguous genetic test results after exome sequencing, or be told that they have VUSs.…”
Section: Discussionmentioning
confidence: 90%